Analisis Perubahan Kerapatan Vegetasi Pegunungan Kendeng Utara Kabupaten Pati Menggunakan Citra Sentinel-2A - Adiguna, Wildansyah Firdaus; Agista, Devi Ega (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2023)
ENGLISHThe landform of Pati Regency’s part of North Kendeng Mountains which is located on the south of Pati Regency (DONE). Land use in this area is dominated by forest areas and dry agricultural land. Reduced vegetation due to misuse of space and resources is a problem that causes geological and hydrological disasters in these mountains and the areas below them. This study aims to determine changes and condition of vegetation area in the North Kendeng Mountains in Pati Regency. The method used to determine the density of vegetation in this study is based on the Normalized Difference Vegetation Index (NDVI) analysis using Sentinel-2A imagery recording in 2017 and 2022. Vegetation conditions are divided into dense, fairly dense, non-dense, non-vegetative, and water/cloud vegetation classifications. Based on the results of image processing, the dense vegetation class did not experience the highest increase in area of 359.68 hectares. The highest decrease in area was found in the fairly dense vegetation class with an area of 243.34 hectares. The decrease in vegetation class decreased by 175.12 hectares. The non-vegetation class increased by 58.51 hectares and the body of water/cloud area increased by 0.27 hectares. The results of the research on the case of land use change in the North Kendeng Mountains in Pati Regency. INDONESIAKabupaten Pati memiliki bentang alam berupa Pegunungan Kendeng Utara yang berada di sisi selatan Kabupaten Pati. Penggunaan lahan di wilayah ini didominasi oleh kawasan hutan dan lahan pertanian kering. Vegetasi yang berkurang akibat kesalahan pemanfaatan ruang dan sumber daya menjadi permasalahan yang menyebabkan timbulnya bencana geologi maupun hidrologi di pegunungan ini dan kawasan di bawahnya. Penelitian ini bertujuan untuk mengetahui perubahan luas dan kondisi vegetasi di Pegunungan Kendeng Utara di Kabupaten Pati. Metode yang digunakan dalam penelitian ini yaitu analisis indeks vegetasi Normalized Difference Vegetation Index (NDVI) dengan memanfaatkan citra Sentinel-2A tahun perekaman 2017 dan 2022. Kondisi vegetasi dibagi dengan klasifikasi vegetasi rapat, cukup rapat, tidak rapat, non vegetasi, dan air/awan. Berdasarkan hasil pengolahan citra, kelas vegetasi tidak rapat mengalami penambahan luas tertinggi, sebesar 359,68 hektar. Penurunan luas tertinggi terdapat pada kelas vegetasi cukup rapat dengan pengurangan seluas 243,34 hektar. Penurunan kelas vegetasi rapat berkurang seluas 175,12 hektar. Kelas non vegetasi bertambah 58,51 hektar dan luas badan air/awan bertambah 0,27 hektar. Hasil penelitian menunjukkan terjadinya peralihan fungsi lahan Pegunungan Kendeng Utara di Kabupaten Pati.